2017
DOI: 10.1589/jpts.29.1134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 4-week balance exercise with medio-lateral unstable sole on ankle joint functional ability

Abstract: [Purpose] This study examined the effects of 4-week of balance exercise with medio-lateral unstable sole on ankle muscle activation and functional ability. [Subjects and Methods] Thirty university students without current or past ankle injuries were assigned to either an experimental group or control group. The experimental group participated in a balance exercise program 3 times a week over 4 weeks, which consisted of one-leg stands and semi-squat exercises with medio-lateral unstable sole. The control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…Clinicians who include balance training as a rehabilitation intervention in subjects with CAI to address sensorimotor control should consider the variety of tasks that can be performed to gain improvements in postural stability. This portion of our results is consistent with Nam et al (2017) that reported after intervention Star Excursion Balance Test scores did not show a significant difference between pre-and postexercise but only differences was in instrumentation that them used star excursion balance test (12).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Clinicians who include balance training as a rehabilitation intervention in subjects with CAI to address sensorimotor control should consider the variety of tasks that can be performed to gain improvements in postural stability. This portion of our results is consistent with Nam et al (2017) that reported after intervention Star Excursion Balance Test scores did not show a significant difference between pre-and postexercise but only differences was in instrumentation that them used star excursion balance test (12).…”
Section: Discussionsupporting
confidence: 93%
“…Functional performance tests range from general lower extremity tests to unilateral hopping tests. Second, the improvement in Y-Balance scores that seen with either rehabilitation protocol conflicts with the findings of an earlier study that used a multicomponent rehabilitation protocol that resulted in significant improvements in scores of Star Excursion Balance Test (12). However, it is likely that the improvements seen in that study stemmed from the balance exercises included in that protocol, rather than the strengthening exercises (2).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Weight bearing exercises cause joint approximation, improve co-contraction of agonist and antagonist muscles, improve movement control, dynamic stability, and neuromuscular control, and improve proprioception and balance (Kisner & Colby, 2002;Sulivan et al, 1982;Sullivan et al, 2001;Voss et al, 1985). Past studies revealed that weight bearing and balancing exercises can improve balance parameters in a posterior-medial direction during standing balancing tests such as the star excursion balance test (Burcal et al, 2019), both the posterior-anterior index and the overall index of balance (Youssef et al, 2018), increased activity of peroneal muscles (Nam & Choi, 2017;Yoshida et al, 2015), decreased ankle instability when landing from a jump (Yoshida et al, 2015), and increased power (Smith et al, 2012). Some studies have reported that these exercises, in combination with other exercises, improve proprioception; however, when these exercises were used alone they did not decrease angle repositioning error (Amrinder et al, 2012;Eils & Rosenbaum, 2001;Ha et al, 2018;Lee et al, 2019;Liu et al, 2012) .…”
Section: Introductionmentioning
confidence: 99%